Body weight status is not a predictive factor of depressive symptoms in Polish adolescents aged 13-18 years - Trambacz-Oleszak, Sylwia; Krzyżaniak, Alicja; Szafrańska- Komarowska, Ineza; Kaczmarek, Maria (Anthropological Review, 2018)
Depression and unhealthy weight status are among the most common concerns in adolescent boys and girls. Research results on the relationship between depression and weight status are contradictory. The aim of the present study was to assess the association between body weight status and depressive symptoms among Polish adolescent boys and girls. The cross-sectional survey was carried out on adolescents attending lower and higher secondary schools located in three medium-sized cities and one big agglomeration in Poland. Anthropometric measurements, such as body height and weight, were performed. Beck Depression Inventory-II (BDI-II) was used to assess depressive symptoms. The total sample consisted of 624 boys and 910 girls aged 13-18 (the mean age was 16.4 ± 1.8) participated in the study. Of them, 73.3% had a healthy weight status, 12.9% were classified as thin, 11.4% were overweight and 2.5% were obese. The prevalence of depression based on BDI-II was 20.2% in boys and 34.9% in girls.The Kruskal–Wallis test revealed a lack of association between the body weight status and total scores of depressive symptoms after controlling for age (p=0.98 and p=0.4 for boys and girls, respectively). The multiple regression analysis revealed that gender and age differentiated the depressive symptoms (for gender: ß=0.19; SE=0.38; p